Problems and Solution Proposals for SMEs in Turkey - Sarp Kaya; Lütfihak Alpkan (Emerging Markets Journal, 2012)
The purpose of this project is to present the problems the SMEs' encounter during providing management and financial requirements, probe how they can solve mentioned problems with as less help as possible within their own organization and offer the employer solutions in micro dimensions. While the SMEs' definitions will be located in the second part, the third part will include the weighting of their advantages and disadvantages. In addition to that, the fourth part will introduce suggestions to solve the problems in question that the SMEs come across. Rounding off, part five will discuss the selection of financial instruments during the stage of providing financial requirements for the SMEs, the mistakes done during their application and offer further solution offers for mentioned problems.